2018
DOI: 10.1016/j.cimid.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Mamastrovirus 5 detected in a crab-eating fox (Cerdocyon thous): Expanding wildlife host range of astroviruses

Abstract: Astroviruses are a common cause of gastroenteritis in children worldwide and can also cause infection in a range of domestic and wild animal species. Canine astrovirus (formally named as Mamastrovirus 5, MAstV5) has been reported worldwide, and its role as an enteric pathogen is still controversial. Herein, we describe the genomic characterization of a MAstV5 (strain crab-eating fox/2016/BRA) identified in a wild canid (Cerdocyon thous) diagnosed with canine distemper virus (CDV) as causa mortis. The nearly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
(54 reference statements)
0
6
1
Order By: Relevance
“…For phylogenetic analysis of our near full-length canine astrovirus sequence, we initially selected the seven most closely related near full-length canine astrovirus sequences from dogs and one mamastrovirus sequence from a fox available in the NCBI Genbank summarized in Table S1. KY765684-CTAV-BRA-2015 16 from a fox did not fall in any cluster with the astroviruses from domestic dogs and was therefore not included in the phylogenetic analyses shown. The generated maximum likelihood (ML) phylogenetic tree (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For phylogenetic analysis of our near full-length canine astrovirus sequence, we initially selected the seven most closely related near full-length canine astrovirus sequences from dogs and one mamastrovirus sequence from a fox available in the NCBI Genbank summarized in Table S1. KY765684-CTAV-BRA-2015 16 from a fox did not fall in any cluster with the astroviruses from domestic dogs and was therefore not included in the phylogenetic analyses shown. The generated maximum likelihood (ML) phylogenetic tree (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). For further analysis we included an additional canine astrovirus sequence from Brazil in year 2013 (KR349489-MAV-V5-BRA-2013) 18 together with the other reference sequences, except KY765684-CTAV-BRA-2015 16 (Table S1). The phylogenetic analysis indicated that the sequences included here fell into 2 clusters with KP404150-CAV-Lincoln-UK-2012, KR349489-MAV-V5-BRA-2013, KX599350-CAV-6-HUN-2012, KP404149-CAV-Gillingham-UK-2012, KX756441-CAV-DD1-AUS-2012 and our DF-BC15-CAV-ORF1b-AUS-2017 in one cluster while KX599349-CAV-2-HUN-2012, KX599351-CAV-115-HUN-2012 and KX599353-CAV-135-HUN-2012 fell in a different cluster based on phylogenetic trees of both nucleotide and amino acid sequences (Figs 5 and 6).…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that there is a positive correlation between CaAstV infection and GID in dogs ( 3 , 4 , 30–32 ). In wild carnivores, CaAstV was coinfected with canine distemper virus (CDV) in crab-eating foxes ( Cerdocyon thous ) showing neurological signs ( 33 ). In addition, coinfection of CaAstV with other enteric viruses, such as canine parvovirus (CPV) and canine coronavirus (CCoV), has also been frequently reported ( 3 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…These foxes seem to be tolerant to human disturbance and are frequently seen in rural areas and close to urban regions. These wild canids have nocturnal scavenger habits and live in close proximity with domestic animals, which may be notable, as domestic host species can play a role in the transmission of infectious agents to wild animals (Alves et al, 2018a;Antunes et al, 2018;Ferreyra et al, 2009;Hübner et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that domestic dogs (Canis lupus familiaris) and wild canids may share viral pathogens, including the rabies virus (RABV) (Antunes et al, 2018;Rocha et al, 2017), canine distemper virus (CDV) (Conceição-Neto et al, 2017;Ferreyra et al, 2009;Hübner et al, 2010;Megid et al, 2009), canine parvovirus 2 (CPV-2) (de Almeida Curi et al, 2010;Hübner et al, 2010), canine coronavirus (Alfano et al, 2019), canine adenoviruses 1 and 2 (Dowgier et al, 2018), and canine https://doi.org/10.1016/j.meegid.2020.104421 Received 21 February 2020; Received in revised form 8 June 2020; Accepted 11 June 2020 astrovirus (Alves et al, 2018a). However, the knowledge about sanitary conditions of these animals are still scarce.…”
Section: Introductionmentioning
confidence: 99%